Recruiting and Retaining Shareholders for Community Supported Agriculture in Texas - Kelsey Hall; Courtney Meyers; David Doerfert; Cindy Akers; Phillip Johnson (Journal of Applied Communications, 2013)
Community supported agriculture provided consumers, known as shareholders, with a share of locally grown products from a farm. Recruiting potential shareholders and retaining current shareholders were challenges for CSA owners since retention rate varied from 20%-70% for CSAs located throughout the United States. The purpose of this study was to explore how Texas CSA shareholders received information about local food and how CSA owners have recruited new consumers and retained existing shareholders. A mixed methods collective case study approach was employed to collect data from an online quantitative survey from shareholders of three CSAs in Texas and qualitative interviews with the CSA owners. Shareholders preferred to search for food choice information on a daily or weekly basis. Websites and interpersonal communication were communication channels sometimes used by shareholders for seeking out information about food choices. CSA owners used a variety of information sources to recruit potential shareholders, including local media, LocalHarvest, events, and word-of-mouth advertising. One of the most common messages delivered to potential shareholders explained the purpose of a CSA. Communication with current shareholders occurred through weekly email newsletters, website, events and conversations. Texas fruit and vegetable producers could use this information in community-based social marketing campaigns to recruit new individuals to join a CSA and retain existing shareholders. Additional research is needed on the information channels preferred by shareholders when learning about the local food movement, particularly CSAs. Research needs to discover CSA owners’ marketing challenges, development of relationships with shareholders, and needed resources.
Keywords: local food; community supported agriculture; community-based social marketing; mixed-methods